TO EVALUATE THE INFLAMMATORY MARKERS IN TYPE 2 DIABETES MELLITUS AND COMPARED IT WITH NORMAL HEALTHY CONTROLS - KAUR, JASWANT; SHWETA; SHARMA, MOHIT; SEEMA; SHAIKH, MOHAMMED NADEEM (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective :To evaluate the serum levels of Interleukin -6, Tissue Necrosis factor – α, C- reactive Protein ( IL-6, TNF- α , CRP) in type 2 diabetes mellitus in North Population Method: A total of 200 participants were selected in this study among them 100 were recruited as Cases who were suffering from T2DM and 100 were healthy controls. Biochemical parameters were analyzed by fully autoanalyser. Serum levels of inflammatory cytokines, TNF-α ,CRP and IL-6 were estimated by ELISA . Data was analyzed using statistical ‘software SPSS 15. TheP<0.05 were considered as statistically significant. Result: in our study we observed that serum levels of candidate cytokines, TNF-α, IL-6 and CRP were highly significant (p<0.001) in T2DM as compared to healthy control. Fasting blood sugar, HbA1c and lipid profile parameters were recorded highly significant (p<0.001) in T2DM as compared to normal healthy controls. Conclusion: Inflammatory cytokines play a significant role in the pathogenesis of T2DM. Hence, these cytokines can be used as early prediction biomarkers which may be helpful in the reduction of mortality rate of T2DM.